A modified thermoplastic polyester elastomer and a method for preparing the same

CN122958684APending Publication Date: 2026-10-23JIANGSU KEYILAI NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611450785.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

该发明采用添加加成型扩链剂,提高聚合物的熔体粘度,从而可以采用先改性再固相缩聚的工艺,提高改性材料的分散效果及与基础树脂的结合力,使获得的产品性能更加优异,但其耐热氧老化性能有待提高

Benefits of technology

[0015]由于采用以上技术方案,本发明的有益效果包括:本发明通过HP-BLaTi催化体系、受阻酚硼酸稳定结构、季戊四醇适度支化结构和端环氧基硅油封端结构共同作用,使得制备的改性热塑性聚酯弹性体表现出优异的力学性能、耐老化性能、耐水解性能和熔体加工稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958684A_ABST
    Figure CN122958684A_ABST
Patent Text Reader

Abstract

The application discloses a modified thermoplastic polyester elastomer and a preparation method thereof, and relates to the technical field of polyester elastomers.The modified thermoplastic polyester elastomer comprises the following raw materials in parts by weight: dimethyl terephthalate 35-40 parts, 1,4-butanediol 25-30 parts, polytetrahydrofuran ether glycol 35-45 parts, 3,5-di-tert-butyl-4-hydroxyphenyl boronic acid 2-3 parts, pentaerythritol 0.1-0.2 parts, HP-BLaTi catalyst 0.05-0.1 parts, and end-capping agent 1-2 parts; the modified thermoplastic polyester elastomer prepared by the application has excellent tensile strength, elongation at break, aging resistance, hydrolysis resistance and good melt processing stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyester elastomer technology, specifically to a modified thermoplastic polyester elastomer and its preparation method. Background Technology

[0002] Thermoplastic polyester elastomers (TPEEs) are block copolymers composed of hard polyester segments and soft polyether or aliphatic polyester segments. They possess the elasticity of rubber and the processability of plastics, and are widely used in automotive parts, seals, and electronic appliances. With the continuous expansion of applications, higher requirements are placed on the heat and oxygen aging resistance, hydrolysis resistance, mechanical strength retention, and processing stability of TPEEs. Existing TPEEs are typically prepared from dimethyl terephthalate, 1,4-butanediol, and polyether glycol as main raw materials through transesterification and polycondensation reactions. During use, these materials are easily affected by factors such as terminal carboxyl groups, oxidation of the soft polyether segments, and hydrolysis of ester bonds, leading to a decline in mechanical properties, surface stickiness, or color darkening. To improve these problems, modification is usually achieved by adding antioxidants, epoxy chain extenders, or organosilicon additives. However, these additives are mostly in physically dispersed form, which can easily lead to insufficient compatibility, migration and precipitation, or decreased long-term stability. Furthermore, the preparation of TPEEs typically uses titanium-based, antimony-based, tin-based, or zinc-based catalysts. While traditional catalysts can promote transesterification and polycondensation reactions, they may trigger side reactions during high-temperature polymerization, leading to a deterioration in the resin's color. Simply increasing the catalyst dosage to shorten the reaction time often results in increased metal residue and decreased material stability.

[0003] Chinese invention patent CN103570928A discloses a modified thermoplastic polyester elastomer and its preparation method. This modified thermoplastic polyester elastomer contains the following components in parts by weight: 100 parts of aromatic dimethyl dicarboxylate, 50-250 parts of aliphatic diol, 50-300 parts of polyether, 1-10 parts of chain extender, 0.1-1 parts of catalyst, 10-500 parts of modifying material, and 5-20 parts of processing aid. This invention uses an addition-type chain extender to increase the melt viscosity of the polymer, thus allowing for a process of modification followed by solid-state polycondensation. This improves the dispersion effect of the modified material and its bonding strength with the base resin, resulting in a product with superior performance. However, its resistance to heat and oxygen aging needs further improvement. Summary of the Invention

[0004] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a modified thermoplastic polyester elastomer and its preparation method.

[0005] A modified thermoplastic polyester elastomer comprises the following raw materials in parts by weight: 35-40 parts dimethyl terephthalate, 25-30 parts 1,4-butanediol, 35-45 parts polytetrahydrofuran ether diol, 2-3 parts 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, 0.1-0.2 parts pentaerythritol, 0.05-0.1 parts HP-BLaTi catalyst, and 1-2 parts end-capping agent; The HP-BLaTi catalyst was prepared by the following method: S1: 3,5-Di-tert-butyl-4-hydroxyphenylboronic acid reacts with triethanolamine to generate HP-BTEA ligand; S2: HP-BTEA ligand reacts with tetraisopropyl titanate to obtain a titanium-containing complex; S3: The reaction of titanium-containing complexes with anhydrous lanthanum acetate yields the HP-BLaTi catalyst.

[0006] The end-capping agent is terminal epoxy silicone oil.

[0007] In step S1, the mass ratio of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid to triethanolamine is 1:(0.6-0.64).

[0008] In step S2, the mass ratio of the HP-BTEA ligand to tetraisopropyl titanate is 3:(2.2-2.5).

[0009] In step S3, the mass ratio of the titanium-containing complex to anhydrous lanthanum acetate is 1:(0.16-0.18).

[0010] In step S1, the reaction is carried out under reflux conditions for 5-6 hours; in step S2, the reaction temperature is 65-75°C and the reaction time is 2.5-3.5 hours.

[0011] In step S3, the reaction temperature is 90-100℃ and the time is 5.5-6.5h.

[0012] A method for preparing a modified thermoplastic polyester elastomer includes the following steps: (1) Weigh out the following by weight: 35-40 parts of dimethyl terephthalate, 25-30 parts of 1,4-butanediol, 35-45 parts of polytetrahydrofuran ether diol, 2-3 parts of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, 0.1-0.2 parts of pentaerythritol, 0.05-0.1 parts of HP-BLaTi catalyst, and 1-2 parts of end-capping agent; (2) Dimethyl terephthalate, 1,4-butanediol and HP-BLaTi catalyst are mixed and subjected to transesterification reaction. Polytetrahydrofuran ether diol, 3,5-di-tert-butyl-4-hydroxyphenylboronic acid and pentaerythritol are added and subjected to polycondensation reaction. End-capping agent is added and subjected to end-capping reaction to obtain material. The material is added to a twin-screw extruder for melt extrusion, and after cooling, pelleting and drying, the material is obtained.

[0013] In step (2), the transesterification reaction is performed as follows: first, the temperature is raised to 185-195℃ and reacted for 1-2 hours, then the temperature is raised to 200-210℃ and reacted for 2-3 hours; the polycondensation reaction is performed as follows: the temperature is raised to 225-235℃ and reacted for 1-1.5 hours, then the temperature is raised to 240-250℃ and reacted for 1.5-2 hours; the end-capping reaction is performed at a temperature of 230-240℃ for a time of 30-40 minutes.

[0014] In step (2), the parameters of the melt extrusion process are set as follows: screw speed is 75-85 rpm, feeding section temperature is 190-200℃, compression section temperature is 210-220℃, melting section temperature is 225-235℃, metering section temperature is 230-240℃, and die head temperature is 230-240℃.

[0015] Due to the adoption of the above technical solutions, the beneficial effects of the present invention include: the present invention, through the combined action of the HP-BLaTi catalytic system, the hindered phenol-boronic acid stabilizing structure, the moderately branched pentaerythritol structure, and the end-capped structure of epoxy-based silicone oil, enables the prepared modified thermoplastic polyester elastomer to exhibit excellent mechanical properties, aging resistance, hydrolysis resistance, and melt processing stability. Attached Figure Description

[0016] Figure 1 The infrared spectrum of the HP-BLaTi catalyst prepared in Example 2 is shown.

[0017] Figure 2 The infrared spectrum of the modified thermoplastic polyester elastomer prepared in Example 5 is shown. Detailed Implementation

[0018] Example 1: Preparation of HP-BLaTi catalyst S1: Under nitrogen protection, 150 ml of anhydrous toluene, 25 g of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, and 15 g of triethanolamine were stirred and mixed. The mixture was heated to reflux for 5 h (water generated during the reaction was continuously removed by a water separator). The mixture was cooled to room temperature and rotary evaporated at 70 °C to constant weight. The crude product was washed with a mixed solution of anhydrous n-hexane and anhydrous ethyl acetate (volume ratio of anhydrous n-hexane to anhydrous ethyl acetate was 8:2) (3 × 50 ml) and dried under vacuum at 70 °C for 8 h to obtain the HP-BTEA ligand. S2: Under nitrogen protection, 250 ml of anhydrous toluene and 30 g of HP-BTEA ligand were stirred and mixed, heated to 65 °C, and 22 g of tetraisopropyl titanate was slowly added dropwise. The addition was completed in 1 h, and the reaction was carried out for 3.5 h. The mixture was then cooled to room temperature and rotary evaporated at 70 °C to constant weight to obtain the titanium-containing complex. S3: Mix 50 ml of anhydrous isopropanol and 8 g of anhydrous lanthanum acetate, disperse by sonication (200 W, 20 kHz) for 20 min, add to 300 ml of anhydrous toluene containing 50 g of titanium complex under nitrogen protection, heat to 90 °C, stir at 250 rpm for 6.5 h, cool to room temperature, rotary evaporate at 70 °C to constant weight, slowly add the crude product to 600 ml of cold anhydrous n-hexane and stir to precipitate, filter, wash the filter cake with cold anhydrous n-hexane (3 × 200 ml), and vacuum dry at 70 °C for 12 h to obtain HP-BLaTi catalyst.

[0019] Example 2 Preparation of HP-BLaTi catalyst S1: Under nitrogen protection, 150 ml of anhydrous toluene, 25 g of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, and 15.5 g of triethanolamine were stirred and mixed. The mixture was heated to reflux for 5.5 h (water generated during the reaction was continuously removed by a water separator). The mixture was cooled to room temperature and rotary evaporated at 70 °C to constant weight. The crude product was washed with a mixed solution of anhydrous n-hexane and anhydrous ethyl acetate (volume ratio of anhydrous n-hexane to anhydrous ethyl acetate was 8:2) (3 × 50 ml) and dried under vacuum at 70 °C for 8 h to obtain the HP-BTEA ligand. S2: Under nitrogen protection, 250 ml of anhydrous toluene and 30 g of HP-BTEA ligand were stirred and mixed, heated to 70 °C, and 24 g of tetraisopropyl titanate was slowly added dropwise. The addition was completed in 1 h, and the reaction was carried out for 3 h. The mixture was cooled to room temperature and rotary evaporated at 70 °C to constant weight to obtain the titanium-containing complex. S3: Mix 50 ml of anhydrous isopropanol and 8.5 g of anhydrous lanthanum acetate, disperse by sonication (200 W, 20 kHz) for 20 min, add to 300 ml of anhydrous toluene containing 50 g of titanium complex under nitrogen protection, heat to 95 °C, stir at 250 rpm for 6 h, cool to room temperature, rotary evaporate at 70 °C to constant weight, slowly add the crude product to 600 ml of cold anhydrous n-hexane and stir to precipitate, filter, wash the filter cake with cold anhydrous n-hexane (3 × 200 ml), and vacuum dry at 70 °C for 12 h to obtain HP-BLaTi catalyst.

[0020] Figure 1 The infrared spectrum of the prepared HP-BLaTi catalyst is shown in the figure. It can be seen from the figure that at 3450 cm⁻¹... -1 A relatively broad absorption peak appears nearby, mainly attributed to the OH stretching vibration absorption of hindered phenolic hydroxyl groups, residual alcoholic hydroxyl groups, and a small amount of adsorbed water; at 2960 cm⁻¹... -1and 2868cm -1 The presence of an aliphatic CH stretching vibration absorption peak nearby indicates that the tert-butyl structure and triethanolamine structure in 3,5-di-tert-butyl-4-hydroxyphenylboronic acid are retained; at 1605 cm⁻¹ -1 An absorption peak for aromatic ring skeletal vibrations appeared nearby, at 1492 cm⁻¹. -1 The presence of absorption peaks related to aromatic ring skeletal vibrations and CH bending vibrations nearby further confirms the existence of the hindered phenolic aromatic ring structure. At 1360 cm⁻¹... -1 1168cm -1 and 1078cm -1 The nearby absorption peaks are mainly related to the stretching vibrations of BO, BOC, and CO / CN, indicating the presence of a boronic ester structure. At 670 cm⁻¹... -1 585cm -1 and 520cm -1 The presence of metal-oxygen correlated absorption peaks nearby, which can be attributed to metal-oxygen correlated vibrational absorptions such as Ti-O, La-O, Ti-OC, and Ti-OB, indicates the introduction of tetraisopropyl titanate and anhydrous lanthanum acetate. These results demonstrate the successful preparation of an HP-BLaTi catalyst containing hindered phenolborate ligands and titanium and lanthanum coordination centers.

[0021] Example 3 Preparation of HP-BLaTi catalyst S1: Under nitrogen protection, 150 ml of anhydrous toluene, 25 g of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, and 16 g of triethanolamine were stirred and mixed. The mixture was heated to reflux for 6 h (water generated during the reaction was continuously removed by a water separator). The mixture was cooled to room temperature and rotary evaporated at 70 °C to constant weight. The crude product was washed with a mixed solution of anhydrous n-hexane and anhydrous ethyl acetate (volume ratio of anhydrous n-hexane to anhydrous ethyl acetate was 8:2) (3 × 50 ml) and dried under vacuum at 70 °C for 8 h to obtain the HP-BTEA ligand. S2: Under nitrogen protection, 250 ml of anhydrous toluene and 30 g of HP-BTEA ligand were stirred and mixed, heated to 75 °C, and 25 g of tetraisopropyl titanate was slowly added dropwise. The addition was completed in 1 h, and the reaction was carried out for 2.5 h. The mixture was cooled to room temperature and rotary evaporated at 70 °C to constant weight to obtain the titanium-containing complex. S3: Mix 50 ml of anhydrous isopropanol and 9 g of anhydrous lanthanum acetate, disperse by sonication (200 W, 20 kHz) for 20 min, add to 300 ml of anhydrous toluene containing 50 g of titanium complex under nitrogen protection, heat to 100 °C, stir at 250 rpm for 5.5 h, cool to room temperature, rotary evaporate at 70 °C to constant weight, slowly add the crude product to 600 ml of cold anhydrous n-hexane and stir to precipitate, filter, wash the filter cake with cold anhydrous n-hexane (3 × 200 ml), and vacuum dry at 70 °C for 12 h to obtain HP-BLaTi catalyst.

[0022] Example 4: Preparation of modified thermoplastic polyester elastomer (1) Weigh the following by weight: 350g of dimethyl terephthalate, 250g of 1,4-butanediol, 350g of polytetrahydrofuran ether diol, 20g of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, 1g of pentaerythritol, 0.5g of HP-BLaTi catalyst (prepared in Example 1), and 10g of end-capping agent (terminated epoxy silicone oil); (2) Dimethyl terephthalate, 1,4-butanediol, and HP-BLaTi catalyst were added to the reactor, and nitrogen gas was introduced to purge the mixture three times. The stirring was then started at 60 rpm to carry out the transesterification reaction. The temperature was first raised to 185℃ and reacted for 2 hours, then raised to 200℃ and reacted for 3 hours. Methanol was continuously distilled off through a distillation column during the reaction. Polytetrahydrofuran ether glycol, 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, and pentaerythritol were added to carry out the polycondensation reaction. The temperature was raised to 225℃, and the stirring speed was adjusted to 50 rpm. The absolute pressure inside the reactor was reduced from atmospheric pressure to 2000 Pa within 40 minutes, and the reaction was carried out for 1.5 hours. Subsequently, the temperature was raised to 240℃, and the stirring speed was adjusted to 30 rpm. At 0 rpm, the absolute pressure inside the reactor was reduced from 2000 Pa to 50 Pa within 15 minutes, and the reaction was carried out for 2 hours. Nitrogen gas was introduced to restore atmospheric pressure, and the temperature was lowered to 230°C. An end-capping agent was added, and the end-capping reaction was carried out for 40 minutes. After cooling to room temperature, the material was crushed at 200 rpm for 8 minutes to obtain the material. The material was added to a twin-screw extruder for melt extrusion. The screw speed was set to 75 rpm, the feeding section temperature was 190°C, the compression section temperature was 210°C, the melting section temperature was 225°C, the metering section temperature was 230°C, and the die head temperature was 230°C. The extrudate was cooled to room temperature in a water bath, pelletized, and vacuum dried at 80°C for 24 hours to obtain the modified thermoplastic polyester elastomer.

[0023] Example 5 Preparation of modified thermoplastic polyester elastomer (1) Weigh the following by weight: 380g of dimethyl terephthalate, 280g of 1,4-butanediol, 400g of polytetrahydrofuran ether diol, 25g of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, 1.5g of pentaerythritol, 0.8g of HP-BLaTi catalyst (prepared in Example 2), and 15g of end-capping agent (terminated epoxy silicone oil); (2) Dimethyl terephthalate, 1,4-butanediol, and HP-BLaTi catalyst were added to the reactor, and nitrogen was introduced to purge the mixture three times. Stirring was then started at 60 rpm to carry out the transesterification reaction. The temperature was first raised to 190℃ and reacted for 1.5 h, then raised to 205℃ and reacted for 2.5 h. Methanol was continuously distilled off through a distillation column during the reaction. Polytetrahydrofuran ether glycol, 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, and pentaerythritol were added to carry out the polycondensation reaction. The temperature was raised to 230℃, and the stirring speed was adjusted to 50 rpm. The absolute pressure inside the reactor was reduced from atmospheric pressure to 2000 Pa within 40 min, and the reaction was carried out for 1.2 h. Subsequently, the temperature was raised to 245℃, and the stirring speed was adjusted to... The absolute pressure inside the reactor was reduced from 2000 Pa to 50 Pa within 15 minutes at 30 rpm, and the reaction was carried out for 1.8 hours. Nitrogen gas was introduced to restore atmospheric pressure, and the temperature was lowered to 235°C. An end-capping agent was added, and the end-capping reaction was carried out for 35 minutes. The mixture was cooled to room temperature and crushed at 200 rpm for 9 minutes to obtain the material. The material was then added to a twin-screw extruder for melt extrusion. The screw speed was set to 80 rpm, the feeding section temperature to 195°C, the compression section temperature to 215°C, the melting section temperature to 230°C, the metering section temperature to 235°C, and the die head temperature to 235°C. The extrudate was cooled to room temperature in a water bath, pelletized, and vacuum dried at 80°C for 24 hours to obtain the modified thermoplastic polyester elastomer.

[0024] Figure 2 The image shows the infrared spectrum of the prepared modified thermoplastic polyester elastomer. As can be seen from the figure, at 3500 cm⁻¹... -1 A relatively broad absorption peak appears nearby, mainly attributed to the OH stretching vibrations of hindered phenolic hydroxyl groups, residual hydroxyl groups, and a small amount of adsorbed water; at 3050 cm⁻¹... -1 and 2910cm -1 The presence of aromatic CH and aliphatic CH stretching vibration absorption peaks nearby indicates that the aromatic ring structure of terephthalic acid ester, the polytetrahydrofuran ether diol segment, and the organic segments from the terminal epoxy-based silicone oil have been introduced into the system. At 1750 cm⁻¹... -1 An absorption peak for the C=O stretching vibration of the ester group appears nearby, at 1016 cm⁻¹. -1 The presence of COC and CO stretching vibration absorption peaks nearby indicates the presence of a polyether ester structure. At 1605 cm⁻¹ -1 The nearby absorption peak is attributed to the C=C skeletal vibration of the aromatic ring, 873 cm⁻¹. -1 The nearby absorption peak is attributed to the out-of-plane bending vibration of the CH group in the aromatic ring of terephthalate, indicating the presence of a hard segment structure in terephthalate. At 1302 cm⁻¹ -1 The nearby absorption peaks are mainly related to CO stretching vibration, methylene bending vibration, and the hindered phenol tert-butyl-related bending vibration, indicating that the hindered phenol structure is preserved. At 800 cm⁻¹... -1The presence of Si-O-Si and Si-C related stretching vibration absorption peaks nearby indicates that the siloxane segments in the terminal epoxy silicone oil have been introduced into the modified thermoplastic polyester elastomer.

[0025] Example 6 Preparation of modified thermoplastic polyester elastomer (1) Weigh the following by weight: 400g of dimethyl terephthalate, 300g of 1,4-butanediol, 450g of polytetrahydrofuran ether diol, 30g of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, 2g of pentaerythritol, 1g of HP-BLaTi catalyst (prepared in Example 3), and 20g of end-capping agent (terminated epoxy silicone oil); (2) Dimethyl terephthalate, 1,4-butanediol, and HP-BLaTi catalyst were added to the reactor, and nitrogen gas was introduced to purge the mixture three times. The stirring was then started at 60 rpm to carry out the transesterification reaction. The temperature was first raised to 195℃ and reacted for 1 h, and then raised to 210℃ and reacted for 2 h. During the reaction, methanol was continuously distilled off through a distillation column. Polytetrahydrofuran ether glycol, 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, and pentaerythritol were added to carry out the polycondensation reaction. The temperature was raised to 235℃, and the stirring speed was adjusted to 50 rpm. The absolute pressure in the reactor was reduced from atmospheric pressure to 2000 Pa within 40 min, and the reaction was carried out for 1 h. Then the temperature was raised to 250℃, and the stirring speed was adjusted to 30 rpm. Within 15 minutes, the absolute pressure inside the reactor was reduced from 2000 Pa to 50 Pa, and the reaction was carried out for 1.5 hours. Nitrogen gas was introduced to restore atmospheric pressure, and the temperature was lowered to 240°C. A sealing agent was added, and the sealing reaction was carried out for 30 minutes. The mixture was cooled to room temperature and crushed at 200 rpm for 10 minutes to obtain the material. The material was then added to a twin-screw extruder for melt extrusion. The screw speed was set to 85 rpm, the feeding section temperature to 200°C, the compression section temperature to 220°C, the melting section temperature to 235°C, the metering section temperature to 240°C, and the die head temperature to 240°C. The extrudate was cooled to room temperature in a water bath, pelletized, and vacuum dried at 80°C for 24 hours to obtain the modified thermoplastic polyester elastomer.

[0026] Comparative Example 1 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as those in Example 5, except that the HP-BLaTi catalyst is replaced with an equal weight of tetraisopropyl titanate.

[0027] Comparative Example 2 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as in Example 5, except that the HP-BLaTi catalyst is replaced with an equal weight of Ph-BLaTi catalyst prepared by the following method: The preparation method of Ph-BLaTi catalyst is basically the same as that in Example 2, except that 3,5-di-tert-butyl-4-hydroxyphenylboronic acid in step S1 is replaced with an equal weight of phenylboronic acid.

[0028] Comparative Example 3 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as in Example 5, except that the HP-BLaTi catalyst is replaced with an equal weight of HP-BLaTi catalyst prepared by the following method: The preparation method of HP-BLaTi catalyst is basically the same as that in Example 2, except that the amount of tetraisopropyl titanate in step S2 is replaced with 18g.

[0029] Comparative Example 4 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as in Example 5, except that the HP-BLaTi catalyst is replaced with an equal weight of HP-BLaTi catalyst prepared by the following method: The preparation method of HP-BLaTi catalyst is basically the same as that in Example 2, except that the amount of tetraisopropyl titanate in step S2 is replaced with 30g.

[0030] Comparative Example 5 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as in Example 5, except that the HP-BLaTi catalyst is replaced with an equal weight of HP-BZnTi catalyst prepared by the following method: The preparation method of HP-BZnTi catalyst is basically the same as that in Example 2, except that anhydrous lanthanum acetate in step S3 is replaced with an equal weight of anhydrous zinc acetate.

[0031] Comparative Example 6 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as in Example 5, except that the HP-BLaTi catalyst is replaced with an equal weight of HP-BLaTi catalyst prepared by the following method: The preparation method of HP-BLaTi catalyst is basically the same as that in Example 2, except that the amount of anhydrous lanthanum acetate in step S3 is replaced with 6g.

[0032] Comparative Example 7 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as in Example 5, except that the HP-BLaTi catalyst is replaced with an equal weight of HP-BLaTi catalyst prepared by the following method: The preparation method of HP-BLaTi catalyst is basically the same as that in Example 2, except that the amount of anhydrous lanthanum acetate in step S3 is replaced with 11g.

[0033] Comparative Example 8 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as those in Example 5, except that the HP-BLaTi catalyst is replaced with a mixture of 0.68g of titanium-containing complex and 0.12g of anhydrous lanthanum acetate.

[0034] Comparative Example 9 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as those in Example 5, except that the end-capping agent (terminated epoxy silicone oil) is replaced with an equal weight of terminated hydroxyl silicone oil.

[0035] Comparative Example 10 The raw material composition and preparation method of the modified thermoplastic polyester elastomer are basically the same as those in Example 5, except that pentaerythritol is replaced with an equal weight of 2-hydroxymethyl-1,3-propanediol.

[0036] The polytetrahydrofuran ether glycol used in the embodiments and comparative examples of this application has a number average molecular weight of 2000. The polytetrahydrofuran ether glycol was pre-dehydrated under vacuum at 100°C and -0.09MPa for 2 hours before use. The epoxy-terminated silicone oil is model 276-4K with an epoxy value of 0.05mol / 100g and is produced by Shanghai Yandi New Material Technology Co., Ltd. The hydroxyl-terminated silicone oil is brand Siwin-OH203 with a hydroxyl content of 8.5% and is produced by Nanjing Silicon Innovation Material Co., Ltd.

[0037] The modified thermoplastic polyester elastomers prepared in the examples and comparative examples were tested for tensile strength, elongation at break, aging performance, hydrolysis resistance, and melt stability.

[0038] Sample preparation: The modified thermoplastic polyester elastomers prepared in the examples and comparative examples were dried in a forced-air drying oven at 110℃ for 5 hours. The samples were then injection molded to meet testing requirements. The temperatures from the feed port to the nozzle were set as follows: 210℃; 220℃; 240℃; 240℃; the mold temperature was 40℃; the material residence time in the barrel was 5 minutes; and the injection speed was 3.6 cm / s. 3 / s; Injection pressure is 50MPa, holding pressure is 80% of injection pressure, and cooling time is 20s. The sample mold dimensions are: total length 170mm, end width 20mm, narrow parallel section width 10mm, narrow parallel section length 80mm, transition arc radius 24mm, and standard thickness 4.0mm.

[0039] Tensile strength and elongation at break tests: The specimens were tested using a CMT4104 universal tensile testing machine at a tensile rate of 50 mm / min. Before testing, the specimens were conditioned for 24 hours at 23℃ and 50±10% relative humidity. Five parallel specimens were tested in each group, and the average value was taken.

[0040] Aging resistance test: First, the tensile strength of the specimens before aging is tested according to the tensile strength test method. Then, the specimens of the same batch are placed in a forced-air thermal aging test chamber for hot air aging treatment at 150℃ for 168 hours. After aging, the specimens are removed and conditioned for 24 hours in an environment of 23℃ and 50% relative humidity, and then the tensile strength after aging is tested. Five parallel specimens are tested in each group, and the average value is taken. The aging resistance performance is expressed as the tensile strength retention rate after aging, calculated by the following formula: Tensile strength retention rate after aging = (Tensile strength after aging / Tensile strength before aging) × 100%.

[0041] Hydrolysis resistance test: First, the tensile strength of the samples before hydrolysis treatment was tested according to the tensile strength test method. Then, the samples of the same batch were completely immersed in deionized water in a constant temperature water bath at 85℃ for 168 hours for hydrolysis treatment. After hydrolysis treatment, the samples were removed, surface moisture was wiped off with filter paper, and the samples were placed in an environment of 23℃ and 50% relative humidity for 24 hours to adjust. Then, the tensile strength after hydrolysis treatment was tested. Five parallel samples were tested in each group, and the average value was taken. The hydrolysis resistance is expressed as the tensile strength retention rate after hydrolysis, calculated by the following formula: Tensile strength retention rate after hydrolysis = (Tensile strength after hydrolysis treatment / Tensile strength before hydrolysis treatment) × 100%.

[0042] Melt stability performance test: The melt flow rate of the samples was tested using a melt flow rate meter at a temperature of 230℃ and a load of 2.16 kg. The initial melt flow rate of the samples was first tested and recorded as MFR0. Then, the melt flow rate of the same batch of samples was tested again after being held in a barrel at 230℃ for 10 minutes and recorded as MFR1. Five parallel samples were tested in each group, and the average value was taken. The change rate of melt flow rate was calculated using the formula: Melt flow rate change rate = [|MFR1 - MFR0| / MFR0] × 100%.

[0043] Table 1 Performance Test Data

[0044] As can be seen from the data in Table 1, the modified thermoplastic polyester elastomer prepared by the present invention has excellent tensile strength, elongation at break, aging resistance, hydrolysis resistance and good melt processing stability.

[0045] The HP-BLaTi catalyst used in this invention contains hindered phenolic borate ligands, a titanium center, and a lanthanum center, forming a composite synergistic catalytic system. The titanium center promotes the transesterification reaction between dimethyl terephthalate and 1,4-butanediol, as well as subsequent polycondensation, improving polymerization efficiency. The lanthanum center coordinates with the carbonyl oxygen, ether oxygen, and hydroxyl oxygen of the ester group, improving the polycondensation matching between hard and soft segments in the reaction system, resulting in more complete polyether ester chain growth and a more uniform chain segment distribution, thereby reducing incompletely polycondensed segments and active end groups. The lanthanum center can stabilize the polyester segments to a certain extent, thereby reducing the possibility of ester bond hydrolysis. At the same time, the coordination of the lanthanum center with the carbonyl oxygen and terminal oxygen can weaken the catalytic effect of the terminal carboxyl group on ester bond hydrolysis, which is beneficial to improving the hydrolysis resistance of the material. The hindered phenolic borate ligand can not only participate in the coordination of the titanium / lanthanum metal center, but also play a thermal stabilizing role in high-temperature polymerization and subsequent processing. Moreover, its hindered phenolic structure can capture free radicals generated during the thermal oxidation of polyether soft segments, inhibit molecular chain breakage, and thus improve the aging resistance and melt stability of the material.

[0046] In this application, 3,5-di-tert-butyl-4-hydroxyphenylboronic acid is added separately during the polycondensation process to further introduce the hindered phenolic and boric acid structures into the polyether ester system. The hindered phenolic structure can improve the material's ability to capture thermo-oxidative free radicals and delay the oxidative degradation of polyether segments. The boric acid structure can form hydrogen bonds, borate ester bonds, or coordination interactions with hydroxyl groups, ether oxygen, or metal coordination centers in the system, enhancing the interaction forces between molecular chains, thereby improving the material's thermal stability and aging resistance. In addition, pentaerythritol can introduce a moderately branched structure during the polycondensation process, which is beneficial to improving the material's melt strength and the degree of molecular chain entanglement, making the material less prone to significant viscosity fluctuations during hot processing such as injection molding and extrusion, while also improving the material's dimensional stability and mechanical strength. Terminal epoxy-based silicone oil is added in the later stage of polycondensation for end-capping. The terminal epoxy-based silicone oil can react with the carboxyl and hydroxyl groups at the polyester chain ends, reducing the content of active end groups in the system and decreasing the catalytic effect of the terminal carboxyl groups on ester bond hydrolysis, thereby improving the material's hydrolysis resistance. Meanwhile, the siloxane segments in the terminal epoxy-based silicone oil possess high flexibility, low surface energy, and good heat resistance, which can improve the material's flexibility, lubricity, and processing stability, enabling the material to maintain good overall performance under high-temperature processing and humid conditions. Therefore, the combined effect of the HP-BLaTi catalytic system, the hindered phenol-boronic acid stabilizing structure, the moderately branched pentaerythritol structure, and the terminal epoxy-based silicone oil end-capping structure results in the prepared modified thermoplastic polyester elastomer exhibiting excellent mechanical properties, aging resistance, hydrolysis resistance, and melt processing stability.

[0047] The catalyst used in Comparative Example 1 lacks hindered phenol-boronate ligands and lanthanum co-centers, resulting in insufficient catalytic stability, chain segment regulation, and antioxidant protection. This leads to incomplete polycondensation and the polyether soft segments are more prone to thermal oxidation and breakage, resulting in poor mechanical properties, aging resistance, hydrolysis resistance, and melt stability.

[0048] In Comparative Example 2, 3,5-di-tert-butyl-4-hydroxyphenylboronic acid was replaced with phenylboronic acid, resulting in the absence of hindered phenolic hydroxyl and tert-butyl steric hindrance structures around the active center of the catalyst. This weakened the coordination effect of the ligand on the titanium / lanthanum metal center and also reduced the free radical capture effect of the hindered phenol. Consequently, the catalytic selectivity and thermal stability of the catalyst decreased during the high-temperature polycondensation process, and the polyether soft segment was more prone to thermal oxidation and breakage, leading to a reduction in the material's aging resistance and melt stability.

[0049] In Comparative Example 3, after reducing the amount of tetraisopropyl titanate, the catalytic activity of the titanium center was insufficient, and the transesterification and polycondensation reactions were not sufficient, resulting in a decrease in the mechanical properties and melt stability of the material.

[0050] In Comparative Example 4, increasing the amount of tetraisopropyl titanate may lead to excessive titanium centers, which could cause chain rearrangement or local degradation, resulting in a decrease in the uniformity of chain distribution and a reduction in the mechanical properties and melt stability of the material.

[0051] In Comparative Example 5, anhydrous lanthanum acetate was replaced with anhydrous zinc acetate. The coordinating ability of the zinc center to the ester carbonyl oxygen, ether oxygen and hydroxy oxygen was weakened, making it difficult to effectively improve the polycondensation matching between the hard segment and the soft segment. The segment stabilizing effect was insufficient, so the mechanical properties, aging resistance, hydrolysis resistance and melt stability were all reduced.

[0052] In Comparative Example 6, reducing the amount of anhydrous lanthanum acetate weakened the synergistic catalysis and coordination regulation of Ti-La, resulting in insufficient uniformity of polycondensation between hard and soft segments. In Comparative Example 7, increasing the amount of anhydrous lanthanum acetate led to residual metal salts or excessive coordination structures causing local over-coordination or uneven dispersion, affecting the regularity of chain segments and the uniformity of the melt. Consequently, the mechanical properties, aging resistance, hydrolysis resistance, and melt stability of both samples decreased.

[0053] In Comparative Example 8, the titanium-containing complex was simply mixed with anhydrous lanthanum acetate. The titanium and lanthanum did not fully form a stable synergistic catalytic structure, resulting in insufficient catalytic activity and dispersion uniformity. Consequently, the mechanical properties, aging resistance, hydrolysis resistance, and melt stability all decreased.

[0054] In Comparative Example 9, terminal epoxy-based silicone oil was replaced with terminal hydroxyl-based silicone oil. The reactivity of terminal hydroxyl-based silicone oil with the terminal carboxyl and hydroxyl groups of the polyester chain was lower than that of terminal epoxy-based silicone oil. This made it difficult to efficiently achieve chain end closure in the later stages of polycondensation, resulting in a higher content of residual terminal carboxyl groups in the material. This easily promotes ester bond hydrolysis, leading to a decrease in hydrolysis resistance. Simultaneously, due to insufficient bonding between the terminal hydroxyl-based silicone oil and the polyether ester backbone, some siloxane segments may exist in a physically dispersed state, resulting in decreased melt stability and mechanical properties.

[0055] In Comparative Example 10, pentaerythritol was replaced with 2-hydroxymethyl-1,3-propanediol, which reduced the number of branching points, weakened the molecular chain entanglement, and resulted in insufficient melt strength and chain segment stability, leading to a decrease in the material's mechanical properties and melt stability.

[0056] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.

Claims

1. A modified thermoplastic polyester elastomer, characterized in that, The ingredients include the following parts by weight: 35-40 parts of dimethyl terephthalate, 25-30 parts of 1,4-butanediol, 35-45 parts of polytetrahydrofuran ether diol, 2-3 parts of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, 0.1-0.2 parts of pentaerythritol, 0.05-0.1 parts of HP-BLaTi catalyst, and 1-2 parts of end-capping agent; The HP-BLaTi catalyst was prepared by the following method: S1: 3,5-Di-tert-butyl-4-hydroxyphenylboronic acid reacts with triethanolamine to generate HP-BTEA ligand; S2: HP-BTEA ligand reacts with tetraisopropyl titanate to obtain a titanium-containing complex; S3: The reaction of titanium-containing complexes with anhydrous lanthanum acetate yields the HP-BLaTi catalyst.

2. The modified thermoplastic polyester elastomer according to claim 1, characterized in that, The end-capping agent is terminal epoxy silicone oil.

3. The modified thermoplastic polyester elastomer according to claim 1, characterized in that, In step S1, the mass ratio of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid to triethanolamine is 1:(0.6-0.64).

4. The modified thermoplastic polyester elastomer according to claim 1, characterized in that, In step S2, the mass ratio of the HP-BTEA ligand to tetraisopropyl titanate is 3:(2.2-2.5).

5. The modified thermoplastic polyester elastomer according to claim 1, characterized in that, In step S3, the mass ratio of the titanium-containing complex to anhydrous lanthanum acetate is 1:(0.16-0.18).

6. The modified thermoplastic polyester elastomer according to claim 1, characterized in that, In step S1, the reaction is carried out under reflux conditions for 5-6 hours; in step S2, the reaction temperature is 65-75°C and the reaction time is 2.5-3.5 hours.

7. The modified thermoplastic polyester elastomer according to claim 1, characterized in that, In step S3, the reaction temperature is 90-100℃ and the time is 5.5-6.5h.

8. A method for preparing a modified thermoplastic polyester elastomer as described in any one of claims 1-7, characterized in that, Includes the following steps: (1) Weigh out the following by weight: 35-40 parts of dimethyl terephthalate, 25-30 parts of 1,4-butanediol, 35-45 parts of polytetrahydrofuran ether diol, 2-3 parts of 3,5-di-tert-butyl-4-hydroxyphenylboronic acid, 0.1-0.2 parts of pentaerythritol, 0.05-0.1 parts of HP-BLaTi catalyst, and 1-2 parts of end-capping agent; (2) Dimethyl terephthalate, 1,4-butanediol and HP-BLaTi catalyst are mixed and subjected to transesterification reaction. Polytetrahydrofuran ether diol, 3,5-di-tert-butyl-4-hydroxyphenylboronic acid and pentaerythritol are added and subjected to polycondensation reaction. End-capping agent is added and subjected to end-capping reaction to obtain material. The material is added to a twin-screw extruder for melt extrusion, and after cooling, pelleting and drying, the material is obtained.

9. The method for preparing a modified thermoplastic polyester elastomer according to claim 8, characterized in that, In step (2), the transesterification reaction is performed as follows: first, the temperature is raised to 185-195℃ and reacted for 1-2 hours, then the temperature is raised to 200-210℃ and reacted for 2-3 hours; the polycondensation reaction is performed as follows: the temperature is raised to 225-235℃ and reacted for 1-1.5 hours, then the temperature is raised to 240-250℃ and reacted for 1.5-2 hours; the end-capping reaction is performed at a temperature of 230-240℃ for a time of 30-40 minutes.

10. The method for preparing a modified thermoplastic polyester elastomer according to claim 8, characterized in that, In step (2), the parameters of the melt extrusion process are set as follows: screw speed is 75-85 rpm, feeding section temperature is 190-200℃, compression section temperature is 210-220℃, melting section temperature is 225-235℃, metering section temperature is 230-240℃, and die head temperature is 230-240℃.

Citation Information

Patent Citations

  • Modified thermoplastic polyester elastomer and preparation method thereof

    CN103570928A